2021
DOI: 10.1017/s0022029921000698
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and aetiology of subclinical mastitis in water buffalo in Bangladesh

Abstract: Subclinical mastitis (SCM) in water buffalo is a production disease associated with decreased milk yield and impaired milk quality and safety. Water buffalo is an important livestock species in Bangladesh, but information about the occurrence and aetiology of SCM in this species is scarce. A cross-sectional study was conducted as part of the Udder Health Bangladesh Programme to (i) determine the occurrence of SCM and bulk milk somatic cell count (SCC) in water buffalo in Bangladesh, (ii) identify pathogens cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
3
11
1
Order By: Relevance
“…Our rate of 11% SCM agrees with values between 5 and 20% that were reported by Joshi and Gokhale [33]. In contrast, the percentage of IMI cases that we detected was 62%, a percentage higher than the 40.4% reported by Singha et al [34] but closer to the value of 63% reported by Moroni et al [5].…”
Section: Discussionsupporting
confidence: 90%
“…Our rate of 11% SCM agrees with values between 5 and 20% that were reported by Joshi and Gokhale [33]. In contrast, the percentage of IMI cases that we detected was 62%, a percentage higher than the 40.4% reported by Singha et al [34] but closer to the value of 63% reported by Moroni et al [5].…”
Section: Discussionsupporting
confidence: 90%
“…Mastitis is a common disease in buffalos that seriously affects milk production and animal health, causing enormous economic loss (23). However, multiple factors, including pathogen infection, unclean environment, nutritional deficiency, and stress reaction, cause mastitis to be difficult to control (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis is a common disease in buffalos that seriously affects milk production and animal health, causing enormous economic loss (23). However, multiple factors, including pathogen infection, unclean environment, nutritional deficiency, and stress reaction, cause mastitis to be difficult to control (23)(24)(25). A gut microbial community containing trillions of microorganisms has been demonstrated to be a complex and interactive ecosystem that participates in the positive regulation of host metabolism and health (22,26).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up genome analysis revealed that the authors had identified a novel Streptococcus species. Singha et al [32] attacked the issue of mastitis in water buffalo through MALDI-TOF biotyping. While clinical mastitis can often be diagnosed by observable changes in the milk quality, udder, and condition of animals, subclinical mastitis remains undetectable in most cases due to lack of obvious clinical signs.…”
Section: Mycoplasmamentioning
confidence: 99%